Performance, Egg Quality, Bone Health, and Immunity Assessments of Lohmann Laying Hens Supplemented with Vitamin D3 in the Diet - Yusuf, G. M.; Sumiati; Mutia, R.; Wardani, W. W.; Akbar, I.; Putri, N. D. S. (Tropical Animal Science Journal, 2023)
Bone health in laying hens is associated with production performance and physical egg quality. This study aimed to evaluate the effects of a diet supplemented with Nutricell Eggstra (vitamin D3 enriched with canthaxanthin) on the production performance, egg quality, bone mineral, and immunity of laying hens. Herein, 150 Lohmann laying hens were divided into three treatments with five replicates. The treatment diets were: T1= diet without Nutricell Eggstra supplementation (control), T2= diet supplemented with 1.00 kg/ton Nutricell Eggstra, and T3= diet supplemented with 1.50 kg/ton Nutricell Eggstra. Compared to the control diet, supplementation of Nutricell Eggstra at doses of 1.00 kg/ton and 1.50 kg/ton significantly increased (p<0.05) hen day production, egg mass, egg index, yolk index, albumen weight, yolk color, eggshell thickness, eggshell strength, vitamin D3 content in egg yolk, heterophil, and heterophil/lymphocyte ratio. Supplementation of Nutricell Eggstra at the studied doses significantly decreased (p<0.05) the feed conversion ratio, yolk weight, eggshell porosity, and lymphocyte content. Nutricell Eggstra supplementation did not affect feed consumption, egg weight, albumen index, albumen weight, eggshell weight, Haugh unit, and tibia bone minerals. In conclusion, supplementation of 1.00 kg/ton Nutricell Eggstra yielded the best performance for Lohmann laying hens aged 36-39 weeks, while supplementation of 1.50 kg/ton Nutricell Eggstra produced the best quality eggs.